Implementasi Kebijakan Pendidikan Bagi Anak Berkebutuhan Khusus di Sekolah Luar Biasa: Tinjauan Literatur Terhadap Tantangan dan Kesenjangan Implementasi - Rahmat Pebrian Jamil; Masbirorotni Masbirorotni; Eddy Haryanto (CV. Global Cendekia Inti, 2026)
The implementation of education policies for children with special needs (CWSN) in Special Schools (SLB) is crucial for achieving inclusive education. This study employs a systematic literature review of 18 articles with thematic synthesis to analyze policy implementation, challenges, and gaps. The main findings indicate that implementation involves school management, curriculum and pedagogical practices, and student services; key challenges include limited teacher competence, inadequate facilities, insufficient funding, and weak coordination among stakeholders; and gaps exist between formal policy and practice, across regions, and in service quality. The study recommends strengthening institutional capacity, enhancing teacher competence, providing adequate facilities, and improving cross sector coordination to enhance implementation quality. The novelty of this research lies in the thematic synthesis that presents a multi level analytical framework for understanding policy implementation in SLB.